Happiness and the human development index: the paradox of Australia - David G. Blanchflower; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2005)
According to the well-being measure known as the U.N. Human Development Index, Australia now ranks 3rd in the world and higher than all other English-speaking nations. This paper questions that assessment. It reviews work on the economics of happiness, considers implications for policymakers, and explores where Australia lies in international subjective well-being rankings. Using new data on approximately 50,000 randomly sampled individuals from 35 nations, the paper shows that Australians have some of the lowest levels of job satisfaction in the world. Moreover, among the sub-sample of English-speaking nations, where a common language should help subjective measures to be reliable, Australia performs poorly on a range of happiness indicators. The paper discusses this paradox. Our purpose is not to reject HDI methods, but rather to argue that much remains to be understood in this area.
Keywords: E6; 330; well-being; happiness; HDI; macroeconomics; Entwicklungsindikator; Lebensqualität; Arbeitszufriedenheit; Australien